The relationship between organizational innovation and performance considering the role of marketing innovation as intermediary variable (Case study: small and medium-sized businesses in the textile industry - Tayebeh Nikraftar (‫مدیریت بازرگانی, 2015)
This study examined the effect of organizational innovation on market innovation and innovation performance. The aim of the present study is to provide a model of organizational marketing performance considering the independent variables, market performance and the intermediary variables of organizational innovation and innovation performance. The questionnaire was designed based on literature review and interviews with experts. The expert panel and confirmatory factor analysis are used to prove the validity of the questionnaire. Statistical data is collected from the entire community including senior executives of 130 businesses- small and medium enterprises in the textile industry in Kashan. 100 questionnaires were completed. The research results suggest that organizational innovation has a direct and significant impact on marketing innovation. However, marketing innovation has no effect on innovation performance. The results also showed a significant correlation between organizational innovation and marketing innovation.